Effecto de un trabajo de aprendizaje del ciclo estriramento - acortamiento sobre la capacidad de salto en voleibol - Palao, J. M.; Saenz, B.; Urena, A. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2001)
The purpose of this study was to become familiar with the effect of jump capacity (execution time and height reached through the center of gravity) produced from a training period using the eccentric-concentric cycle of the flexors and extensors of the foot through exercise techniques done in an integrated manner within training. This study was achieved using 12 volleyball players at the national level and dividing them randomly into two groups (experimental and control). All of the players took part in the same training during the duration of the study (the first major competitive cycle). The experimental group further worked at the end of the warm-up of the training period three days per week for 14 weeks. Before and after the training period, subjects participated in a control battery, where they recorded the height reached and the time of momentum in the eccentric and concentric phase. The experimental group achieved an improvement (decrease) in eccentric contraction time and in total momentum time in the test of lateral blocking movement without crossing (p<0.05). With respect to the height reached, a difference was not found in the two groups. The effect of a training period produces a temporary gain in the blocking action of lateral movement without crossing in volleyball applying the same levels of force (height reached).